EXPLORATION OF CHILDREN’S LEARNING EXPERIENCES AGED 5-6 YEARS THROUGH THE STEAM APPROACH PROJECT OF MAKING CRISPY SHRIMP - Mustakimah; Qonitah thifal (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Early childhood is a golden age where children’s potential develops rapidly through appropriate stimulation. One crucial life skills rarely explored academically is cooking. This research aims to explore the implementation of the STEAM (Science, Technology, Engineering, Art, and Mathematics) approach to improving basic everyday skills through a crispy shrimp making project. This research used a qualitative design with a case study approach. Subjects included children aged 5-6 years at ABA 54 Kindergarten in Semarang. Data were collected through participant observation,in depth interviews,and activity documentation. The research results show that the crispy shrimp project successfully integrated all five aspects of STEAM. Science emerges through ingredient identification, technology through the use of cooking utensils, engineering through the sequence of cooking steps,art through the aesthetics of presentation,and mathematics through measuring ingredients. Overall,this activity proved effective as a holistic learning medium that stimulates children’s curiosity,problem solving skills,and creativity. These findings confirm that the practical,project based STEAM approach not only develops cognitive and motor skills but also shapes children’s character and independence,preparing them for future generations.